2013
DOI: 10.1007/s11104-013-1628-x
|View full text |Cite
|
Sign up to set email alerts
|

Trace element uptake dynamics for maize (Zea mays L.) grown under field conditions

Abstract: Background and aims The trace element uptake process of plants is a key factor in assessing the risks of trace element build-up in agricultural soils. Scarce information exists on the trace element dynamic uptake of plants grown in the field, especially on those potentially hazardous. In this study, the uptake process of As, Cd, Cu, and Zn in maize plants was quantified and characterized throughout the entire season. Methods Along two seasons, the uptake dynamics of field-grown maize plants in absorbing the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In turn, Zhuang et al [45] demonstrated higher bioconcentration factors for zinc and cadmium compared with lead and copper, which is in line with the present study. Molina et al [46] reported that cadmium and zinc were more mobile from soil to plant compared with copper and arsenic. Martínez-Trujillo and Carreón-Abud [36] also found higher BCFs and translocation factors for chromium after applying nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Zhuang et al [45] demonstrated higher bioconcentration factors for zinc and cadmium compared with lead and copper, which is in line with the present study. Molina et al [46] reported that cadmium and zinc were more mobile from soil to plant compared with copper and arsenic. Martínez-Trujillo and Carreón-Abud [36] also found higher BCFs and translocation factors for chromium after applying nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, models of plant uptake have been proposed for organic [52,53] and inorganic [54,55] contaminants at contaminated sites to define the risk to human health.…”
Section: Influence Of Soil Characteristics On Plant Uptakementioning
confidence: 99%
“…Although Z. mays and H. annuus are not considered as species that specifically accumulate As (like P. vittata), they show an increasing uptake when the concentration of plant-available As increases in the soil (Molina et al, 2013;Woolson, 1973). Indeed, relatively high As concentrations (Table 1) reflected an accumulation in the roots, pointing to a potential transfer into the plant system.…”
Section: Arsenic Accumulation In the Roots Of Z Mays And H Annuusmentioning
confidence: 99%